2016
DOI: 10.1080/02615479.2016.1237628
|View full text |Cite
|
Sign up to set email alerts
|

Are you ready? Qualifying social work students’ perception of their preparedness to work competently with service users from sexual and gender minority communities

Abstract: Social workers come into contact with lesbian, gay and bisexual (LGB) and trans people in all areas of their practice and across all service user groups. In line with professional requirements, social work educators must ensure that students who complete qualifying programmes successfully meet the standards expected of them as registered social workers, including those around diversity.This study aims to explore the extent to which qualifying social work students feel prepared to practise competently with peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Positive experiences and student satisfaction on placement tend to be associated with getting regular feedback on performance, feeling empowered as a learner with some autonomy, and being able to observe constructive role models (Bogo et al, 2004). Placement research does however highlight the multi-faceted nature of preparedness, encompassing confidence in some aspects of practice and less in others (Kamali et al, 2017), the value of curriculum training (Moylan & Wood, 2017) and role of life experiences beyond the university curriculum in contributing to preparedness for social work placement (Inch, 2017). Oliver et al (2017) foregrounds the issue of social work students' confidence to speak up and engage in difficult conversations about placements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Positive experiences and student satisfaction on placement tend to be associated with getting regular feedback on performance, feeling empowered as a learner with some autonomy, and being able to observe constructive role models (Bogo et al, 2004). Placement research does however highlight the multi-faceted nature of preparedness, encompassing confidence in some aspects of practice and less in others (Kamali et al, 2017), the value of curriculum training (Moylan & Wood, 2017) and role of life experiences beyond the university curriculum in contributing to preparedness for social work placement (Inch, 2017). Oliver et al (2017) foregrounds the issue of social work students' confidence to speak up and engage in difficult conversations about placements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While confident in their abilities on the whole, the majority of school health practitioners, including social workers, reported limited or no experience in discussing behavioural health concerns or addressing harassment faced by LGBTQ students (Mahdi et al, 2014). In a small-scale qualitative study with 10 social work students in Southern England, participants reported feeling generally prepared to work with sexual minority clients (Inch, 2017). However, they did not attribute this feeling of preparedness to classroom teaching but to experience in working with sexual minority clients on placement (Inch, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In a small-scale qualitative study with 10 social work students in Southern England, participants reported feeling generally prepared to work with sexual minority clients (Inch, 2017). However, they did not attribute this feeling of preparedness to classroom teaching but to experience in working with sexual minority clients on placement (Inch, 2017). In fact, the students in this study recalled very little classroom teaching on LGBT issues (Inch, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nation composition of samples We investigated 165 effective samples, in which the ethnic composition included 8 ethnic groups of Zhuang, Han, Yao, Hui, Tibetan, Yankee family, Dong, and Miao, and its basic structure was shown in the following table [4]. In the 166 valid samples, the Han occupied the majority, accounting for 66.1%; Zhuang was the second, accounting for 23.6%; and Yao ranked the third, accounting for 5.5% [5].…”
Section: Introductionmentioning
confidence: 99%